2005
DOI: 10.1007/s11096-004-4771-x
|View full text |Cite
|
Sign up to set email alerts
|

When Fever, Paracetamol? Theory and Practice in a Paediatric Outpatient Clinic

Abstract: Our study showed that the management of feverish children was globally correct in the Paediatric Emergency Department, but several improvement measures have been taken (e.g. tables of normal and abnormal ranges of temperature, recommended temperature measurement techniques, dosage regimen of antipyretic drugs, guidelines to parents), justifying the implementation of a pharmaceutical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Excessive concern about cerebral damage and other consequences of fever is also seen in healthcare professionals [25,30-32]. In one study, less experienced paediatricians were more likely to succumb to parental anxiety and subsequently give them inappropriate advice – in this case alternating ibuprofen and paracetamol – compared with more experienced paediatricians [33].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Excessive concern about cerebral damage and other consequences of fever is also seen in healthcare professionals [25,30-32]. In one study, less experienced paediatricians were more likely to succumb to parental anxiety and subsequently give them inappropriate advice – in this case alternating ibuprofen and paracetamol – compared with more experienced paediatricians [33].…”
Section: Introductionmentioning
confidence: 99%
“…In 11% of the children treated, the daily dose was at a level that could cause severe toxicity [36]. In contrast, a Swiss study revealed that fever was often undertreated, especially by nurses and even more so by parents [30]. Underdosing may lead to unnecessary, repeated clinic and/or emergency room visits [36].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations